Impact of EGFR genetic variants on glioma risk and patient outcome - Costa, Bruno Marques (2011)
B.M. Costa and M. Viana-Pereira contributed equally to this work; The authors thank the Immunochemotherapy Department of Hospital S. Marcos, and Clinica Laboratorial Dr. Edgar Botelho Moniz, S. Tirso, Portugal, for their helpful assistance in the management of controls